2004
DOI: 10.1210/en.2003-1707
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Facilitates Neurite Extension via Apolipoprotein E in Cultured Adult Mouse Cortical Neurons

Abstract: Literature review suggests a close relationship between estrogen and apolipoprotein E (ApoE) in the central nervous system. Epidemiology studies show that estrogen replacement therapy (ERT) decreases the morbidity from several chronic neurological diseases. Alleles of ApoE modify the risk for and progression of the same diseases. ApoE levels in the rodent brain vary during the estrous cycle and increase after 17beta-estradiol administration. Both estradiol and ApoE3, the most common isoform of human ApoE, incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
71
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 53 publications
8
71
0
Order By: Relevance
“…These findings are consistent with previous reports of Finch and colleagues (15) who demonstrated that E 2 increased ApoE in cells isolated from CNS and by other investigators in vivo (16)(17)(18). In this study, we demonstrated that ApoE expression is differentially regulated by ER␣ and ER␤.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…These findings are consistent with previous reports of Finch and colleagues (15) who demonstrated that E 2 increased ApoE in cells isolated from CNS and by other investigators in vivo (16)(17)(18). In this study, we demonstrated that ApoE expression is differentially regulated by ER␣ and ER␤.…”
Section: Discussionsupporting
confidence: 94%
“…E 2 had no effect on neurite outgrowth in neuron cultures from mice lacking the ApoE gene or mice transgenic for human ApoE4. In contrast, E 2 significantly increased neurite growth of neurons in culture from mice transgenic for human ApoE3 (16). Although the ApoE2͞3 and ApoE4 genotypes responded differently to E 2 -induced neuritic sprouting, E 2 induced an increase in ApoE expression regardless of genotype (16).…”
Section: E2-regulated Apoe Expression Is Mediated By Er and Is Er Isomentioning
confidence: 87%
See 3 more Smart Citations